Analisis Risiko Produksi Tepung Tapioka pada CV Harum Mekar Kabupaten Pati - Majiid, Shofina Laila; Setiadi, Agus; Setiyawan, Hery (Universitas Galuh, 2026)
Tapioca flour production at CV Harum Mekar fluctuates. This condition causes losses, so the company needs to address the risks that occur. This study aims to analyze the level of risk, analyze the occurrence and sources of production risks, and to analyze effective mitigation strategies to address risks in the tapioca flour production process at CV Harum Mekar. The study was conducted in September-October 2025 at CV Harum Mekar. The location was determined purposively based on the consideration that the company is engaged in the agribusiness sector. The research method used is a case study with a quantitative approach. The sampling method uses purposive respondents consisting of 7 key informants. Data analysis uses the coefficient of variance (CV) and House of Risk (HOR). The results are that the risk level at CV Harum Mekar is classified as very high with a CV value of 39.88%. HOR Phase 1 indicates there are 15 risk events and 22 risk sources. The priority sources of risk obtained are lack of accuracy of packaging and storage workers, climate change, too high cassava prices, leaking storage warehouse roofs, less than optimal water quantity during the extraction process, intensive water change frequency, less dense grater eyes, unbalanced flour supply with flash dryer temperature, too much water quantity during the separation process and flour that falls on the floor is repackaged. Risk management strategies obtained 12 strategies with 5 priority strategies, namely more intensive Standard Operating Procedure (SOP) training in each field for employees, more careful supervision at each stage of production, more intensive SOP training for machines for employees, making warehouse maintenance and machine replacement schedules and making contracts with cassava farmers.